Over a undertanding irational - Filho, Márcio Francisco Rodrigues (2015)
Present here that Schopenhauer understands nature as a concept built by man, abstract and conceptual: a word. Schopenhauer reformulated transcendental idealism of Kant to the concepts of understanding did not make reference to sensitivity, because animals have experience of the phenomenal world, contrary to what Kant's theory leads us to believe. After all, in Kant, animals would have to deal with concepts to represent objects, which Schopenhauer denies. In Schopenhauer's theory our perceptions do not need the categories of understanding (concepts, language) to draw the object of possible experience and become representation. The Kantian understanding will be shown as a hybrid object: through representation, middle thing-in-itself, as Kant mixed thinking and intuition, making the experience and the dependent objective world of understanding (conceptual). But for Schopenhauer the individual object, perceptions are independent of abstract thought. The thought engages with concepts and abstract what is common objects, causing them. But the understanding is irrational, intuitive and perceptive.